2004
DOI: 10.1097/01.aud.0000111545.71693.48
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Steady-State Responses and Word Recognition Scores in Normal-Hearing and Hearing-Impaired Adults

Abstract: IAFM responses are significantly correlated with WRS and may provide an objective tool for examining the brain's ability to process the auditory information needed to perceive speech.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
3
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 76 publications
5
74
3
1
Order By: Relevance
“…Digital hearing aids offer more features and flexibility to meet the varied needs of hearing-impaired individuals by using non-linear signal processing algorithms (e.g., wide dynamic range compression), directional microphones, and noise reduction algorithms. Studies have shown that aided speech recognition is better than unaided speech recognition (e.g., Dimitrijevic, John, & Picton, 2004;Walden, Grant, & Cord, 2001). Importantly, however, hearing-aid users are still reported to display inferior performance in auditory speech recognition compared to their counterparts with normal hearing (cf.…”
Section: Impact Of Hearing Loss On Speech Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Digital hearing aids offer more features and flexibility to meet the varied needs of hearing-impaired individuals by using non-linear signal processing algorithms (e.g., wide dynamic range compression), directional microphones, and noise reduction algorithms. Studies have shown that aided speech recognition is better than unaided speech recognition (e.g., Dimitrijevic, John, & Picton, 2004;Walden, Grant, & Cord, 2001). Importantly, however, hearing-aid users are still reported to display inferior performance in auditory speech recognition compared to their counterparts with normal hearing (cf.…”
Section: Impact Of Hearing Loss On Speech Recognitionmentioning
confidence: 99%
“…Importantly, however, hearing-aid users are still reported to display inferior performance in auditory speech recognition compared to their counterparts with normal hearing (cf. Dimitrijevic et al, 2004). The adverse effects of age-related hearing loss on auditory speech recognition also greatly depend on the type of speech stimuli (Lash, Rogers, Zoller, & Wingfield, 2013;Whitmer & Akeroyd, 2011).…”
Section: Impact Of Hearing Loss On Speech Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect has been shown on both young and adult listeners with HL (Arlinger, 2003;Hicks & Tharpe, 2002;Tun, McCoy, & Wingfield, 2009). In addition, several studies have shown that hearing aids do not fully restore speech difficulties of individuals with HL (e.g., Dimitrijevic et al, 2004;Moradi, Lidestam, Hällgren, & Rönnberg, 2014;Nakeva von Mentzer, 2014), which made perceiving speech stimuli cognitively demanding (Moradi et al, 2014;Rönnberg et al, 2013).…”
Section: Cognitive Consequences Of Hlmentioning
confidence: 99%
“…The ASSR is an important procedure of auditory evaluation, because it presents more facilities and efficiency to obtain responses, objectivity in the register analysis, selectivity in the responses frequency, and higher detection of hearing responses than other objective methods such as BAEP (13) . Such findings justify the importance of the ASSR, because young children may not cooperate during the behavioral auditory evaluation and this procedure is useful to determine the auditory threshold, once there is close relationship between the electro physiological thresholds obtained through ASSR and behavioral thresholds (14) .…”
Section: Introductionmentioning
confidence: 99%